Penggunaan Teknologi Finansial Syariah Dalam Laporan Keuangan - Desi Saraswati; Adela Yanuar Zahrani; Reza Diva Primadani; Nova Artha Mevia; Anggita Putri Pramesti; Riskya Vernanda Pratama; Ahmad Nurrohim (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research explores the development and use of Islamic fintech in financial reporting in Indonesia. Islamic fintech, which integrates Islamic principles with financial technology, has shown significant growth, particularly given Indonesia's status as the country with the largest Muslim population. Using a qualitative descriptive research method, this study examines how Islamic fintech facilitates transparency, efficiency, and financial inclusion while adhering to Islamic principles such as avoiding riba, gharar, and maisir. The findings indicate that Islamic fintech has enhanced the quality of financial reporting through technologies like blockchain, enabling real-time transaction tracking. However, challenges such as uneven distribution and dynamic regulations remain obstacles. This research provides insights into how Islamic fintech can refine the governance of Islamic finance, emphasizing the need for cooperation among government, regulators, and industry to maximize the potential of Islamic fintech in improving the efficiency and effectiveness of the Islamic financial market.